Otonomi Daerah - Nurhayati, Nurhayati; Sumiyati, Sumiyati; Juariyah, Juariyah; Paramitha, Paramitha; Syamsiah, Syamsiah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
Regional autonomy is a new system of governance that emerged as a result of reform. This is a way to build and empower regions in accordance with the progress and conditions of society. Various aspects of democracy are currently developing in Indonesia. This strategy is used as a countermeasure against the economic and trust crises that have caused a shift in political power in Indonesia. Along with the implementation of regional autonomy in Indonesia, regional autonomy and its problems have become the subject of growing discussion. Although regional autonomy is an ideal idea for the Republic of Indonesia, it does not mean that it can be implemented without problems. Because our country is currently still in a transitional stage, the implementation of regional autonomy and its problems are still the subject of research for academics and government practitioners. Indonesian. In the book Regional Autonomy: Problems and Solutions in Indonesia, it is stated that the negative effects of regional autonomy are the emergence of conflicts between regional and central governments and opportunities for people at the regional level to commit various violations. In addition, there is a difference between areas that are still developing and those with high incomes. Undoubtedly, regional autonomy in Indonesia still faces many problems. Undoubtedly, these problems must be addressed and resolved so that the main objectives and noble values of regional autonomy can be achieved and realized properly.